2005
DOI: 10.1515/znc-2005-9-1013
|View full text |Cite
|
Sign up to set email alerts
|

Ovipositional Deterrent on Mature Stage of Sweet Pepper, Capsicum annuum, against Liriomyza trifolii (Burgess)

Abstract: Liriomyza trifolii (Burgess), the American serpentine leafminer fly, is a well-known serious pest in the world. This insect species attacks plants of more than 21 families including Solanaceae plants. A sweet pepper, Capsicum annuum (Solanaceae), on mature stage, however, shows resistance to this leafminer fly. This resistance is based on the ovipositional deterrent in the sweet pepper leaf against the fly species. Based on the bioassay guided fractionation, phytol [(2E)-3,7,11,15-tetramethyl-2-hexadecen-1-ol]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…4,5) Induced resistance against pathogens has recently been investigated in many plant species, 6) and research on its application to crop protection has also been conducted. 7) This resistance is caused by an accumulation of secondary metabolites, expression of pathogenesis-related genes and proteins, generation of reactive oxygen species and other unknown processes.…”
mentioning
confidence: 99%
“…4,5) Induced resistance against pathogens has recently been investigated in many plant species, 6) and research on its application to crop protection has also been conducted. 7) This resistance is caused by an accumulation of secondary metabolites, expression of pathogenesis-related genes and proteins, generation of reactive oxygen species and other unknown processes.…”
mentioning
confidence: 99%
“…Further, the release of volatile compounds and defense against phytophagous insects may be another reason for reduced fecundity (Frantz et al, 2004;Kashiwagi et al, 2005). The number of eggs significantly varied among the chillies accessions.…”
Section: Fig1 Non-preference For Whitefly Bemisia Tabaci Adult Settlmentioning
confidence: 99%
“…5) While conducting a survey of host selection for L. trifolii in a greenhouse, we observed that the leaves of sweet pepper (Capsicum annuum) at a mature stage were rarely attacked by this insect. 9) On the other hand, this species attacks the young leaves of sweet pepper. We have previously reported luteolin 7-O--D-apiofuranosyl-(1 !…”
mentioning
confidence: 99%
“…We have previously reported luteolin 7-O--D-apiofuranosyl-(1 ! 2)--D-glucopyranoside 9) and phytol {(2E)-3,7,11,15-tetramethyl-2-hexadecen-1-ol} 10) from the methanol extract of mature C. annuum leaves as ovipositional deterrents against this insect species. In the course of isolating these deterrents, we reported the presence of activity in the aqueous fraction.…”
mentioning
confidence: 99%